Revisión de los Programas para la Inclusión Educativa con Niños Con Necesidades Educativas Especiales - Chávez Eras, Andrés (2017)
The aesthetic innovation within the educational units of the third level, demands an organization of physical, material and financial resources, which can only be done by the administration. The social inclusion of children deserves an analysis of the different contexts that will lead to a very clear criterion of the environmental and genetic origin of many of the realities that are being lived and how the teacher in the fields of Ecuadorian education, will include those plans, the different strategies that must be taken in the classroom for this basic rehabilitation to take place. In the brain of people with Asperger, 70% of communication between people is non-verbal language, 30% is done literally, Asperger's maintain 30% of the literal form. The Asperger is not visible, but they have a repetitive system, they do not look in the eyes. For this reason, a survey has been prepared with fieldwork for students of the third and fourth grade Párvulos School of the University of Guayaquil.